2007
DOI: 10.1111/j.1475-4991.2007.00251.x
|View full text |Cite
|
Sign up to set email alerts
|

The Distributional Consequences of Government Spending and Taxation in the U.S., 1989 and 2000

Abstract: We assess the effects of government expenditures and taxation on household economic well-being in the United States in 1989 and 2000. Net government expenditure is estimated as the difference between government expenditures incurred on behalf of the household sector-transfers and public consumption-and the taxes paid by that sector. We incorporate the estimates of net government expenditures into a wealth-adjusted measure of income. We find that overall inequality in our income measure is considerably reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
41
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 19 publications
(18 reference statements)
2
41
1
Order By: Relevance
“…Wolff and Zacharias (2007) emphasize that net government spending reduces income inequality in a considerable manner and the effect is owed more to expenditures than to taxes. Bertola (2010) argues that Europe's Economic and Monetary Union (EMU) had a small (althout significantly positive) impact on income inequality, partially reflecting the implementation of less generous social policies.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Wolff and Zacharias (2007) emphasize that net government spending reduces income inequality in a considerable manner and the effect is owed more to expenditures than to taxes. Bertola (2010) argues that Europe's Economic and Monetary Union (EMU) had a small (althout significantly positive) impact on income inequality, partially reflecting the implementation of less generous social policies.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Especially for lower quantiles, average expenditure always seems to lie much higher than average income. This is not only true for the five countries observed here, as indicated by the unbelievably low savings rate for all countries in the first decile in Table 11, but also for the U.S. (Wolff & Zacharias, 2007). Sabelhaus (1993) measured savings alternatively as the difference between the change in assets and the change in liabilities and found that this method, although theoretically equivalent to income minus expenditures, yields very different results.…”
Section: Disposable Income or Expenditures?mentioning
confidence: 73%
“…They reported that the effect of cash transfers was three times greater than the effect of tax incidence 10 in reducing the level of dispersion between market income and disposable income (OECD 2012a andJoumard, Pisu, andBloch 2012). Earlier studies by Wolff and Zacharias (2007) on the effects of US government expenditures and taxation on household incomes from 1989 to 2000 reached a similar conclusion-compared with taxes, expenditures yielded greater inequality-reducing results. Among transfers, the progressivity of housing benefits was substantial, but its redistributive impact was inadequate due to limited magnitude (OECD 2012a, OECD 2012b, and OECD 2012c.…”
Section: Public Cash Transfers and Benefitsmentioning
confidence: 89%